Parkinson risk in idiopathic REM sleep behavior disorder: preparing for neuroprotective trials - Postuma, Ronald B; Gagnon, Jean-Francois; Bertrand, Josie-Anne; Génier Marchand, Daphné; Montplaisir, Jacques Y (Neurology, 2015)
To precisely delineate clinical risk factors for conversion from idiopathic REM sleep behavior disorder (RBD) to Parkinson disease, dementia with Lewy bodies, and multiple system atrophy, in order to enable practical planning and stratification of neuroprotective trials against neurodegenerative synucleinopathy. In a 10-year prospective cohort, we tested prodromal Parkinson disease markers in 89 patients with idiopathic RBD. With Kaplan-Meier analysis, we calculated risk of neurodegenerative synucleinopathy, and using Cox proportional hazards, tested the ability of prodromal markers to identify patients at higher disease risk. By combining predictive markers, we then designed stratification strategies to optimally select patients for definitive neuroprotective trials. The risk of defined neurodegenerative synucleinopathy was high: 30% developed disease at 3 years, rising to 66% at 7.5 years. Advanced age (hazard ratio [HR] = 1.07), olfactory loss (HR = 2.8), abnormal color vision (HR = 3.1), subtle motor dysfunction (HR = 3.9), and nonuse of antidepressants (HR = 3.5) identified higher risk of disease conversion. However, mild cognitive impairment (HR = 1.8), depression (HR = 0.63), Parkinson personality, treatment with clonazepam (HR = 1.3) or melatonin (HR = 0.55), autonomic markers, and sex (HR = 1.37) did not clearly predict clinical neurodegeneration. Stratification with prodromal markers increased risk of neurodegenerative disease conversion by 200%, and combining markers allowed sample size reduction in neuroprotective trials by >40%. With a moderately effective agent (HR = 0.5), trials with fewer than 80 subjects per group can demonstrate definitive reductions in neurodegenerative disease. Using stratification with simply assessed markers, it is now not only possible, but practical to include patients with RBD in neuroprotective trials against Parkinson disease, multiple system atrophy, and dementia with Lewy bodies.